Kontribusi Bambu terhadap Pendapatan Perajin Kerajinan Bambu Desa Kayubihi, Kecamatan Bangli, Kabupaten Bangli - PUTRA, I KADEK ADIKA ARJASTA; ANTARA, MADE; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
The Contribution of Bamboo to Bamboo Craftsmen Income in Kayubihi Village, Bangli District, Bangli Regency The wealth of Indonesian forests is so diverse. Forests provide substantial benefits for society. One of the leading forest commodities is bamboo. Bamboo provides many benefits for local communities. Communities in Kayubihi Village produce various types of bamboo handicrafts as a source of livelihood. This study aims to identify the types of bamboo handicrafts produced by the craftsmen, to analyze the added value of bamboo, and to analyze the contribution of bamboo to the craftsmen’s income in Kayubihi Village. This study uses simple random sampling technique, which involves 86 respondents. The analysis techniques used are both qualitative and quantitative. The results of this study indicate that sokasi has the highest added value among all products, namely Rp 87,774.73 per unit, followed by cake packaging at Rp 24,666.17 per set, and bakul at Rp 18,151.68 per unit. The contribution of bamboo to Kayubihi Village communities’ monthly income is 88%. It is recommended that governments help to market bamboo handicrafts. Craftsmen should continue to run and develop bamboo handicraft production by adding new innovations. Communities should work together for the sustainability of bamboo plants.  Further research by students and researchers on the contribution of bamboo to the society’s income in Kayubihi Village is needed.